Stillbirth rates, trend and distribution in the Volta region, Ghana: findings from institutional data analysis, 2018–2022 - Chrysantus Kubio; Williams Azumah Abanga; Ignatius Aklikpe; Dzidefo Kofi Agbavor; Victor Zeng; Samuel Adolf Bosoka; Desmond Klu; Senanu Kwesi Djokoto (BMC Pregnancy and Childbirth)
Abstract Background Stillbirth is an adverse pregnancy outcome with devastating effects on families. Integration of essential interventions at all levels of the healthcare system has reduced stillbirths globally. Stillbirths are still recorded in the Volta Region. Reviewing institutional stillbirth data may reveal the regional burden and help in planning relevant strategies to reduce its occurrence. This study determined the stillbirth rate and its distribution in the Volta Region of Ghana. Methods A review of institutional stillbirths in the Volta Region from 2018 to 2022 was done using data extracted from the District Health Information Management System 2 database. The variables extracted were the type of stillbirth, district, and year. Microsoft Excel 2016 and ArcGIS 10.4 were used for the data analysis. Descriptive statistics were performed with results presented in a table, graph, and map. Results A total of 1,885 stillbirths were recorded in the Volta Region over the study period and majority were macerated 58.7% (1,106/1,885). The regional stillbirth incidence was 10.0 per 1,000 births with the district rate between 0.8 and 19.9 per 1,000 births. The highest incidence was recorded in North Tongu District. There was a general decline in stillbirth rate over the period from 11.2 per 1,000 births in 2018 to 8.8 per 1,000 births in 2022. Conclusion Stillbirths in the Volta region were low and declined over the study period. Majority of stillbirths were macerated. North Tongu district reported the highest incidence of stillbirth. The Regional Public Health Department could train midwives and community health nurses working in the observed high rate districts on quality antenatal care and detection of poor intrauterine fetal growth.